Central configurations of the circular restricted 4-body problem with three equal primaries in the collinear central configuration of the-3 body problem - Llibre, Jaume (Trends in Computer Science and Information Technology, 2021)
In this paper we classify the central configurations of the circular restricted 4-body problem with three primaries with equal masses at the collinear configuration of the 3-body problem and an infinitisimal mass.